Information seeking and perceptions of anxiety and pain among women undergoing hysterosalpingography. (July 2016) - Handelzalts, Jonathan E.; Levy, Sigal; Peled, Yoav; Binyamin, Liat; Wiznitzer, Arnon; Goldzweig, Gil; Krissi, Haim
Abstract: Objective: Hysterosalpingography (HSG) is an accepted diagnostic tool for infertility workup and is considered an invasive procedure that is generally regarded as uncomfortable and painful, though research on psychological consequences is scarce and outdated. The study objective was to investigate women's experience of HSG in terms of fear, anxiety and pain, as compared to colposcopy. Study design: This cross sectional questionnaire study was conducted at two public women's health clinics in Israel between January 2013 and March 2014. 137 women were included in the study. 42 consecutively sampled women referred for outpatient HSG and 95 consecutively sampled women referred for outpatient diagnostic colposcopy. The main outcome measures were: state-trait anxiety, information seeking behavior, fear of pain, fear of the results, retrospective pain. Results: Compared to those undergoing colposcopy, women undergoing HSG expressed significantly higher anxiety prior to the procedure, feared the pain involved more, and rated the procedure as more painful retrospectively. HSG patients tended to report a higher degree of information seeking. Information seeking was correlated with higher anxiety among HSG but not colposcopy patients. Conclusion(s): HSG is a highly stressful procedure associated with fear, anxiety, pain and information seeking. Research is needed to find possible ways of ameliorating these emotions and behaviors as they may have negative impact on patient cooperation.